Digital Literacy of Elementary School Students Based on Sundanese Culture - Hidayat, Dicky; Satyani, Irva Sectio Cesaria; Amalia, Putu Anggi; Dewasandra, Shafira Andzani (Tadbir : Jurnal Studi Manajemen Pendidikan, 2024)
Digital literacy plays a significant role in the internalization of Sundanese cultural values through animated videos on the YouTube platform. This research aims to determine the level of digital literacy skills among elementary school students in Bandung. This study is a type of quantitative research. The variable in this research is the digital literacy skills of students measured using the Likert Scale. The population consists of 4th, 5th, and 6th-grade students at Griya Bandung Indah Elementary School. The sample was determined using the Random sampling technique, with a sample size of 114 students. The data collection technique used is in a form of a questionnaire. Data analysis was performed using descriptive data analysis techniques with the SPSS program. The results of the data analysis show the digital literacy skills of students in the indicator of accessing information with a percentage of 60,5%.The digital literacy skills of students is the indicator of understanding information with a percentage of 57,9%. The digital literacy skills of students in the indicator of creating information with a percentage of 52,6%. The digital literacy skills of students in the indicator of communicating information with a percentage of 57,0%. The digital literacy skills of students in the indicator of evaluating information with a percentage of 74,6%. The digital literacy skills of students is an indicator of cultural understanding with a percentage of 71,9%. The digital literacy skills of students in the indicator of security with a percentage of 67,5%. This research addresses a gap in research, as no previous studies have specifically examined the digital literacy skills of elementary school students in Bandung in relation to the internalization of Sundanese cultural values through YouTube animated videos. This research provides new insight into how digital media supports the preservation and promotion of local culture.